Avaliação da qualidade das águas superficiais e metodologia para determinação de bacias críticas em áreas do cerrado: exemplo da região das nascentes do rio Araguaia, GO - Barbosa, Priscila Maia (2015)
The water is an essential resource for the existence of life. The multiple uses of this resource, as well as the type of land use present in areas drained by rivers can affect the quality of its waters. The establishment of a framework on water in Brazil occurred in 1934 with the creation of the Water Code, later the Federal Constitution of 1988 and the National Water Resources Policy 1997 contributed to the standardization of water uses. Classification and use of water based on law allowed the establishment of physical, chemical and biological acceptable quality, according to their class and use. Indicators and Water Quality Indices are important tools for identifying pollution and/or contamination of the water, so present themselves as instruments in the management of water resources. In view of the pressure that water resources are suffering and the intensification of land use for agricultural activities in areas of Cerrado, this research aimed to identify critical sub-basins as the quality of surface waters in Goias sector of basis waters of the Araguaia river. Therefore, the research methodology is based on a literature review on the topic Water Quality, Environmental Processes in River Basin, Water Quality Indicators and Critical Areas; thematic maps, land use, the Water Quality Index - IQA and critical sub-basins were prepared in a GIS environment, through ArcGIS 10 program; Two field work to collect samples were carried out in eleven sub-basins at the beginning and end of the rainy season with multiparameter equipment; reading the temperature parameters, total dissolved solids (TDS), hydrogen potential (pH), dissolved oxygen (DO) and redox potential (Eh) were performed in the field, and the analysis of nitrate and phosphorus parameters performed in laboratory; to get the results was performed the analysis of water quality and comparison with land use sub-basin; application of the IQA, statistical analysis using the Pearson correlation coefficient, and identification of critical sub-basins. The sub-basins studied exhibited high rates of anthropic use in your area as a whole and in the riparian zone. All subbasins had values above the established by CONAMA to match. The results pointed to the interference of land use, climate seasonality and the physical and natural attributes on water quality. It was noticed that the sub-basins with more expressive use of pasture also showed the worst water quality and sub-basins with more training in forest riparian areas tended to have better water quality. Overall, the methodological procedures used were presented to support efficient research on the quality of water and allowed to verify different levels of impairment of water quality of the sources of the Araguaia river. In this sense, the identification of critical sub-basins, based on the understanding of the interrelationship between the different variables that make up the open system of a watershed is an important mechanism for planning, management, and monitoring of water resources.